The Effectiveness of CALL in EFL Learning: A Synthesis of Empirical Evidence - Usman, Andi Syamsurijal; Salsabila, Hanania (Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia, 2025)
Technology integration has been shown to enhance learners' language proficiency by creating authentic learning environments, fostering confidence, and improving technological skills. This literature review explores the effectiveness of computer-assisted language learning (CALL) in enhancing EFL learning, addressing learning gaps, and offering global perspectives on CALL implementation. the present study conducts a systematic literature review to synthesize empirical findings on the impact of CALL on EFL learning outcomes and to identify pedagogical and contextual factors mediating its effectiveness. Drawing on more than 70 peer-reviewed studies published between 1991 and 2025 and indexed in Scopus, ERIC, and Google Scholar, the review encompasses quantitative, qualitative, and mixed-methods research. The selected studies were analyzed using thematic synthesis to trace recurring patterns across language skills development, learner engagement, autonomy, and technology-enhanced instructional practices. The synthesis indicates that CALL is associated with consistent gains in vocabulary, grammar, listening, speaking, reading, and writing, particularly when embedded within blended learning designs, scaffolded pedagogical tasks, and technologies offering adaptive and timely feedback. At the same time, the effectiveness of CALL appears contingent upon the quality of instructional design, teachers’ digital pedagogical competence, and institutional support structures. Overall, the review suggests that CALL constitutes a robust pedagogical approach to EFL instruction when implemented through principled design and sustained professional development. Persistent challenges related to digital inequality and uneven teacher preparedness underscore the need for systemic investment to ensure equitable and sustainable CALL integration.